Emissions based tolls: impacts on the total emissions of an intercity corridor - Sampaio, Carlos (2021)
Around 70% of the transport-related emissions in the EU came from road transportation. A major contribution to the transport-related emission externalities comes from all the passenger car trips generated in intercity corridors. The main objective of this paper is to explore alternative road sharing solutions to reducing externalities from individual transportation in intercity corridors without increasing the cost each user would pay to travel through the Motorway. Specifically, it intends to assess how generalised GPS-based toll systems can reduce system emissions compared with a flat-electronic collection system. Simulation experiment results on a case study in Portugal comprising alternative routes of approximately 60 km show the proposed GPS-based toll (with different strategies for peak and off-peak hour) can influence the total emissions with only a small decrease of the total revenue without sacrificing the cost that each user would pay to travel through this corridor.